2017
DOI: 10.3329/bjp.v12i1.30417
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine supplementation ameliorates serum tumor necrosis factor-alpha and matrix metalloproteinase-3 in knee osteoarthritis women

Abstract: <p class="Abstract">Seventy-two females with mild to moderate knee osteoarthritis were included in this randomized double-blind placebo-controlled study. Patients in the intervention group (n=36) received L-carnitine supplement (750 mg/day) for two months. L-Carnitine supplementation led to decrease in serum TNF-α and MMP-3 levels significantly in comparison with the baseline (p&lt;0.001 and p&lt;0.001, respectively) and placebo group (p&lt;0.001 and p=0.03, respectively). In addition, physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Three studies were conducted to examine the average changes in reported l ‐carnitine supplement consumption on quality of life in people with OA in their knees. [ 24,26,27 ] For Figure 3c, the overall effect test result was ( Z = 1.87, p = 0.06). Figure 3c shows the variation in body weight between the trial group ( n = 90 participants: l ‐carnitine) and the control group ( n = 97 participants: placebo) relative to the first point (MD = −1.21, 95% CI [−4.25, 1.83]; Z = 0.78; p = 0.43).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Three studies were conducted to examine the average changes in reported l ‐carnitine supplement consumption on quality of life in people with OA in their knees. [ 24,26,27 ] For Figure 3c, the overall effect test result was ( Z = 1.87, p = 0.06). Figure 3c shows the variation in body weight between the trial group ( n = 90 participants: l ‐carnitine) and the control group ( n = 97 participants: placebo) relative to the first point (MD = −1.21, 95% CI [−4.25, 1.83]; Z = 0.78; p = 0.43).…”
Section: Resultsmentioning
confidence: 92%
“…A systematic review and meta‐analysis comprised four trials that examined the average changes in laboratory measurements in individuals with OA of the knee who were using l ‐carnitine supplementation. [ 22,24,26,27 ] For Figure 3 a, the whole overall effect test result was ( Z = 0.07, p = 0.95). The differences in high‐density lipoprotein cholesterol (HDL‐C) from baseline between the 67 participants in the l ‐carnitine experimental group and the 72 participants in the placebo‐control group are shown in Figure 3a (mean difference [MD] = −3.71, 95% CI [−7.90–0.48]; Z = 1.73; p = 0.08).…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Also, Abd-Allah et al showed that administration of lcar returned testicular NO and serum IL-2 to normal levels in a lipopolysaccharide model of sepsis [82]. Another evidence indicated that l-car supplementation has benefcial efects on reducing TNF-α levels in knee osteoarthritis patients [91]. More correlational evidence pointed out that lcar administration in drinking water signifcantly decreased the bleomycin-induced elevations of serum TNF-alpha and LPO level in lung tissues [92].…”
Section: Discussionmentioning
confidence: 99%
“…Group of few other studies have demonstrated that LC is effective in reducing plasma as well as serum levels of TNF-α. 30,31 It can be suggested that LC produce anti-apoptotic effects at lower doses only just like TNF-α showed more apoptotic effects at lower doses. But the mechanism by which LC could inhibit TNF-α induced apoptotic effects in lower doses only is yet to be confirmed in further studies.…”
Section: Discussionmentioning
confidence: 99%